Luxury in Education: How Service Features and Customer Perceptions Drive Loyalty and Purchase Decisions in Prestigious Schools - Fitrhanefi, Muhyi Nur; Adiwijaya, Karto (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The study aims to analyze the impact of luxury perception on purchasing behavior in the premium educational sector. A quantitative research method was employed using a survey distributed to 336 parents of students enrolled in top five luxury elementary schools in Greater Jakarta. Respondents were selected using purposive sampling based on predefined inclusion criteria, such as being the primary decision-maker for school enrollment and having children currently enrolled in these schools. The findings reveal that price, service quality, prestige, and extraordinary experience significantly influence luxury perception, with service quality emerging as the dominant factor. Data were analyzed using SEM-PLS approach. This research provides practical insights into developing marketing strategies for luxury educational services by emphasizing a balance between objective service features and subjective customer perceptions.